1972
DOI: 10.1073/pnas.69.6.1540
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma Proteins as Tumor-Specific Transplantation Antigens

Abstract: MATERIALS AND METHODSImmunogens and Immunization Schedules. 10-to 12-week old female BALB/cAnN mice were injected with purified myelomaproteins 315 or 460, which were isolated by subjection of the proteins to mild reduction and alkylation (in this work with iodoacetic acid) (2, 3). Proteins 315 and 460 purified in this manner (820w,, = 6.5) have about eight carboxymethyl groups per molecule (150,000 daltons), one on the C-terminal or penultimate cysteine of the light chain and 3-4 on the heavy chain (4). Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0
1

Year Published

1975
1975
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(132 citation statements)
references
References 11 publications
4
127
0
1
Order By: Relevance
“…The tumour used in this study presents tumour-specific and tumour-associated antigens (Lynch et al, 1972;Comoglio and Forni, 1973) which can be employed to induce resistance in syngeneic animals. Previous work also indicated that the take and growth of this tumour is influenced LU e by spontaneous or artificially induced changes in host immune reactivity .…”
Section: Discussionmentioning
confidence: 99%
“…The tumour used in this study presents tumour-specific and tumour-associated antigens (Lynch et al, 1972;Comoglio and Forni, 1973) which can be employed to induce resistance in syngeneic animals. Previous work also indicated that the take and growth of this tumour is influenced LU e by spontaneous or artificially induced changes in host immune reactivity .…”
Section: Discussionmentioning
confidence: 99%
“…The first generation of Id vaccines consisted of purified Id or Id protein conjugated to an immunogenic carrier protein, such as keyhole limpet hemocyanin (KLH), 3 injected together with an immunologic adjuvant. Vaccination with these vaccines conferred protection against tumor challenge in a number of lymphoma and myeloma animal models (1)(2)(3)(4). Based on these preclinical results, immunization with autologous Id has been initiated in clinical trials to control residual disease in B cell lymphoma and multiple myeloma (5)(6)(7).…”
mentioning
confidence: 99%
“…However, for this critical step to be reached, it was first necessary to demonstrate that idiotypic determinants present in the immunoglobulin borne by FL cells can serve both as a tumor-and patient-specific antigen ( Fig. 1; [3,4]). Subsequently, it was shown that immunization of FL patients against such a self-antigen was possible [5] and induced an idiotype-specific, humoral [5][6][7][8] and cellular [6,7,9] immune response.…”
Section: Introductionmentioning
confidence: 99%